GENGGAM JARIMU : Promosi edukasi relaksasi genggam jari sebagai upaya menurunkan intensitas nyeri sendi - Asni Hasaini; Muhlisoh Muhlisoh; Martini Nur Sukmawaty (INDRA: Jurnal Pengabdian kepada Masyarakat, 2023)
One of the independent interventions that is effective in reducing joint pain in gout arthritis is finger grip relaxation, this relaxation is easy to do. The purpose of implementing this community service is that the community and health cadres are able to recognize gout arthritis and finger grip relaxation, and health cadres are able to understand the measurement of pain scales using the Numerical Rating Scale (NRS). The service was carried out in the village of Tunggul Irang for 3 (three) months, namely measuring pretest and posttest knowledge, measuring uric acid levels, promoting education about gout arthritis and relaxation of finger grips through media stickers and demonstration methods, teaching pain scale measurements to health cadres, then the monitoring stage evaluation for 1 week. The knowledge of the villagers and health cadres about gout arthritis and finger grip relaxation was in the very good category and the majority of uric acid levels were in the normal category and the health cadres had a good understanding of measuring pain scales. Promotion of education optimized both in a structured and gradual manner can increase knowledge and the right choice of complementary therapy to prevent the risk of gout arthritis.